Analysis of Factors Affecting Stock Returns with Economic Value Added as Intervening Variables in Property and Real Estate Companies Listed on the Indonesia Stock Exchange - Richard Richard; Iskandar Muda; Sirojuzilam Sirojuzilam (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
This study aims to determine the effect of cash flow, debt to equity ratio (DER), return on assets (ROA), and stock beta on stock returns with economic value added as intervening variables in Property and Real Estate Companies listed on the Indonesia Stock Exchange for the 2010-2020 period. The population used in this study were 65 Property and Real Estate Companies listed on the Indonesia Stock Exchange. The sampling method is by using purposive sampling. Based on the criteria that have been made, the number of samples is 11 companies so that a total of 121 research observations are obtained. Hypothesis testing in this study using regression analysis and to test the significance of the coefficient t test.  The results of this study indicate that: (1)cash flow has a negative and insignificant effect on stock returns, (2)DER has a negative and insignificant effect on stock returns, (3)ROA has a positive and significant effect on stock returns, (4)stock beta has a negative and significant effect on stock returns, (5)cash flow, DER, ROA, and stock beta through economic value added have a significant effect on stock returns.